The phonic method for improving students’ speaking ability - Mawaddah Ulya; Rita Mahriza; Siti Habsari Pratiwi (Institut Agama Islam Negeri Langsa, 2021)
The study was underlain by the child's introduction to letters performed by memorization, in which the children find it difficult to know it in sequence. Therefore, the purpose of this study was to increase children's ability to know the letters through phonic methods. The study applied the Class Action Research (CAR) Method with a model of Kemmis and Taggart. The data collection technique used is observation and test. The result of the study showed that a child could recognize the vowel and consonants. However, no child can recognize the initial letter sounds of the images of objects contained on the card, and there was no child able to combine letters into syllables and words at the pretest stage. In cycle I, there are 12 children able to recognize the vowel and consonant letters, 13 children can recognize the initial letter sounds of the images of objects contained on the cards, and 12 children can combine letters into syllables and words. In cycle II, there are 17 children able to recognize vowel and consonant letters, 16 children can recognize the initial letter sounds of the images of objects contained on the cards, and 15 children can combine letters into syllables and words. Thus the application of the phonic method can improve child-speaking ability.